Quantitative analysis of cefixime via complexation with palladium(II) in pharmaceutical formulations by spectrophotometry - Syed Najmul Hejaz Azmi; Bashir Iqbal; Nada Said Hassan Al-Humaimi; Iman Rashid Saif Al-Salmani; Noora Ali Saad Al-Ghafri; Nafisur Rahman (Elsevier, 2013)
An optimized and validated spectrophotometric method has been developed for the determination of cefixime in pharmaceutical formulations. The method is based on the complexation reaction between cefixime and palladium ion in the presence of acidic buffer solution (pH 3) in ethanol-distilled water medium at room temperature. The complex absorbed maximally at 352nm. Beerâs law is obeyed in the working concentration range of 2.5â35Î¼g/mL with apparent molar absorptivity of 1.015Ã104L/molcm and Sandellâs sensitivity of 0.001Î¼g/cm2/0.001 absorbance unit. The limits of detection and quantitation for the proposed method are 0.175 and 0.583Î¼g/mL, respectively. The effect of common excipients used as additives has been studied in the determination of cefixime. The proposed method has been successfully applied for the determination of cefixime in pharmaceutical formulations. The results obtained by the proposed method were statistically compared with the reference method using t and F values and found no significant difference between the two methods. Keywords: Spectrophotometry, Cefixime, Palladium ion, Pd(II)âcefixime complex